Analisis Yuridis terhadap Sengketa Hak Milik Atas Tanah: (Studi Putusan Nomor 120/Pdt.G/2023/PN.Jkt.Brt) - Fransiskus Rifandy Moa; Gunawan Djajaputera (CV Rewang Rencang, 2024)
Land disputes are legal issues that arise due to conflicts or clashes of interest among parties concerning the control, use, or ownership of land. These disputes have become an inevitable issue in modern society, particularly given the increasing demand for land driven by population growth, urbanization, and economic development. The research method employed in this study is normative juridical, which focuses on the examination of library materials or secondary data. This data includes documents, legislation, and various literatures relevant to the legal topic or issue under investigation. Land disputes often stem from differing interpretations regarding the legal status of certain parcels of land, particularly concerning ownership and usage rights. Several primary factors triggering land disputes can be summarized as follows: (1) The lack of proper land administration in the past; and (2) Structural imbalances in land control and ownership. Efforts to resolve legal issues related to land disputes are explicitly regulated under Presidential Regulation No. 20 of 2015 concerning the National Land Agency (Badan Pertanahan Nasional or BPN). Specifically, Article 3 clauses (3) and (4) of this regulation mandate the Head of the National Land Agency to formulate and implement policies in several strategic areas. The resolution of land disputes is generally pursued through legal means by bringing the case to court. Additionally, land disputes may also be resolved through negotiation or mediation, which offers several advantages compared to judicial proceedings. One of the primary benefits of resolution through negotiation is the efficiency in terms of time, cost, and effort required. The aim of the research conducted by the author is to identify the causative factors and resolution efforts concerning land ownership disputes.